Is Surveillance Endoscopy Necessary after Colectomy in Ulcerative Colitis?. (2nd July 2011) - Shuno, Yasutaka; Hata, Keisuke; Sunami, Eiji; Shinozaki, Masaru; Kawai, Kazushige; Kojima, Tetsu; Tsurita, Giichiro; Hiyoshi, Masaya; Tsuno, Nelson H.; Kitayama, Joji; Nagawa, Hirokazu
Abstract : The role of surveillance endoscopic followup in colectomized patients with long standing total colitis is controversial. Here, we aimed to clarify its usefulness for the early detection of dysplasia and cancer in this group of patients. Ninety-seven colectomised UC patients followedup by surveillance endoscopy were retrospectively investigated by reviewing the pathological reports. Patients had received either subtotal colectomy and ileo-rectal anastomosis (IRA) or total proctocolectomy and ileal anal anastomosis (IPAA). Definite dysplasia was diagnosed in 4 patients, who had received IRA; among them, 2 were carcinoma with submucosal invasion, and one was a high-grade dysplasia. Postoperative surveillance endoscopy is useful for the detection of early cancer in the remaining colonic mucosa of UC patients, and those receiving IRA, in which rectal mucosa is left intact, would be good candidates. However, its effectiveness for patients receiving IPAA, in which the rectal mucosa is resected, needs further investigation.